Student mobility: Extent, impacts and predictors of a range of movement types for secondary school students in England. (18th May 2022) - Prior, Lucy; Leckie, George
Abstract: Moving school is a major event for students, with potential impacts on both student and school performance. Students can experience a diversity of move types, including variation in timing, origin and destination, though this complexity is not always acknowledged in studies or educational policies, which tend towards binary distinctions of movers versus non‐movers. However, it is crucial to understand the vulnerabilities and outcomes associated with different mobility types, including to inform more effective and efficient targeting of support. We therefore study the extent, impacts and predictors of a diverse range of school moves during secondary schooling for a cohort of students completing their end‐of‐school examinations in 2018/2019 in England. We highlight a negative association between mobility and achievement for all movement types, however, we find substantial heterogeneity in the strength of their association with student performance and highlight the likelihood of making different types of school moves vary by student characteristics. Therefore, we recommend the wider consideration and examination of diverse mobility features by research and in educational accountability systems.